Fenomena Perilaku Konsumtif di Era Digital dalam Perpektif Psikologi Islam - Cahyani, Pramesti (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
The phenomenon of consumer behavior in the digital era has become a major concern due to advances in technology and social media that influence people's lifestyles. Consumer behavior is often driven by the desire to meet social standards and achieve instant gratification, resulting in waste and negatively impacting mental health. In Islam, consumer behavior is defined as israf, an excessive attitude that contradicts the values of convenience. From an Islamic psychology perspective, spiritual approaches such as patience and gratitude are effective solutions to address this behavior. Patience teaches self-restraint and emotional control, while gratitude encourages individuals to appreciate God's blessings and utilize them wisely. This study aims to analyze the phenomenon of consumer behavior in the digital era from an Islamic psychology perspective through a literature review method. The results are expected to provide theoretical and practical contributions in developing a holistic approach to addressing consumer behavior.